Day 3 Wed, May 02, 2018 2018
DOI: 10.4043/28844-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges Facing the Industry in Offshore Facility Decommissioning on the California Coast

Abstract: This paper addresses the challenges of decommissioning oil and gas facilities offshore California, where there are a number of large, deep-water platforms, and decommissioning infrastructure and services are severely lacking. The regulatory process for decommissioning platforms is also very complex and expensive and the prospects for reefing platform jackets are uncertain at best. These circumstances have created a situation that the domestic oil and gas industry has not really faced before, i.e., that the cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In addition to cost, Ars and Rios [30] reported that future liability and government regulations contribute to the reasons why the expected decommissioning rate has never been achieved. Therefore, companies are currently facing major challenges and risks in the planning and execution of decommissioning projects [31]. These include:…”
Section: Systems For Decommissioning and Environmental Impactmentioning
confidence: 99%
“…In addition to cost, Ars and Rios [30] reported that future liability and government regulations contribute to the reasons why the expected decommissioning rate has never been achieved. Therefore, companies are currently facing major challenges and risks in the planning and execution of decommissioning projects [31]. These include:…”
Section: Systems For Decommissioning and Environmental Impactmentioning
confidence: 99%
“…According to Byrd et al (2018), the state of Qatar established regulations that sought to ensure the safety of all those accessing the country's seabed which may impact the future implementation of the R2R approach. Accordingly, reefing oil platforms in the EEZ of Qatar will lead to several legal challenges (da Fonseca et al, 2020).…”
Section: Implementation Determinants Of Rig-to-reefmentioning
confidence: 99%
“…Rig-to-reef is meant to offer favorable environmental conditions for fish and other macroinvertebrate communities to thrive but with the increased oil and gas exploration, the project would pose significant legal, logistical, and environmental challenges to stakeholders (Lim, 2021). Byrd et al (2018) noted that the development of artificial reefs on any oilfield requires the removal of the top structures while leaving behind those buried deep in the sea.…”
Section: Implementation Determinants Of Rig-to-reefmentioning
confidence: 99%